Communication Strategy in Coral Reef Conservation Program by NGO KPLB to Belitung Society - Saputra, Ade Afrilian; Bakti, Andi Faisal (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2023)
In order to see the strategic communication, it must be viewed from a variety of factors that influence the communication processes. These factors are communicators, messages, media to convey that message, communicant, and the effects that occur after the messages was delivered. I am interested in knowing the strategic communications made by the NGO KPLB in coral reef conservation program submitted to the Belitung coastal communities island. This research is a study of multimedia journalism, which describes how the relationship communication elements are communicators, messages, media, communicant, and effects create an effective communication process. The method used in this study is a descriptive qualitative approach. Data retrieval techniques include observation, interviews and documentation validity of the data was verified using s source triangulation. Communicators, message, media, communicant and effects are interrelated to create an effective communication process. The results reveal that proximity as a psychological factor is important to make a communicant interested in receiving the message. The existence of the message of economic change and alternative livelihood delivered lead to the fishermen readiness to participate in coral reef conservation program.